COVID-19 and lifestyle in childhood - Palma-Lozano, Diana (2021)
The COVID-19 pandemic has caused several alterations in the rhythm of life of the world population: confinement, changes in family dynamics, restrictions, closure of schools, parks, recreation centers, suspension of sports and workshops; changes that led to a significant reduction in physical activity of children, which is considered a key component for optimal physical and healthy development of the body. This situation increases the sedentary lifestyle and, thus, the risk of developing metabolic and systemic problems due to the lack of movement.